Space allocation in a Philippine 17th century bahay na bato - Tombo, Dahlia Y.; Mayo, Adelaida Villaraza (1995.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Research paper (ID 199)--University of the Philippines Diliman.
Keywords: Domestic architecture -- Philippines; Space (Architecture) -- Philippines